Crianças conectadas ao YouTube : vivências na cultura digital - Costa, Aliana França Camargo (2022)
Having as its direction the study in digital culture, this thesis aims to understand what exists in the relationship between children, aged between 7 and 10 years, and the digital media YouTube. Digital technologies have transformed the ways we interact. The internet as the fabric of our lives (CASTELLS, 2015) boosted a new reorganization in which children, based on new digital media and with the emergence of the social network YouTube, in 2005, were able to enter mass personal communication, expanding their practices. For the circulation, production, exhibition and, above all, in the consumption of information, which we consider a new communicational ecology. This research uses netnography (KOZINETS, 2014) with ethnographic inspiration, understanding that the study was in two contiguous fields: in the offline presence, when we enter the space organized and facilitated by a municipal school, located in the city of Barra do Garças - MT, between the months of august and november 2019, to get closer to our subjects; and in the online field, when we analyzed YouTube channels, which the 11 participating children indicated accessing more frequently. We systematized the findings that were projected into three major dimensions: What children watched the most, with regard to preferences for channels and youtubers; How they appropriated digital technologies for social interaction with YouTube; and finally, Why did children consume information from the platform, in which we present the problematizations and perceptions. As theoretical support, we rely on Vygotsky's scientific project (1999a; 2003; 2004; 2006; 2008; 2009; 2018) for which the social and cultural intertwine in the human constitution. The guiding line of our analysis is the concept of perejivanie [experience] that is part of the last phase of studies of the Belarusian thinker, and is considered one of the most important concepts of Vygotsky's work, when he understands that his study should be return to the semantic field, of meanings, to understand the higher formation of the mind. Perejivanie is what lies between the personality and the environment in which the child develops. Within the concept, the emotion-personal elements, affections, imagination engender the folds of consciousness experienced by the individual. Through the experience [perejivanie] we analyzed the speeches of children under the light of Espinosa's theory (2000) articulating with Vygotsky's research, to delve deeper into the affections that are contained in the relationship of children with the digital media YouTube. In addition, we approach the concept of perejivanie to the style of digital culture in which technological aesthetics ascend (MAFFESOLI, 1995; SANTAELLA; ARANTES, 2008), thus creating a digital experience. In digital culture, the child social agent remodeled his experience, appropriating technology and bringing experiences aligned with the new way of feeling, provided by the aesthetic style.